2019
DOI: 10.18038/aubtda.498606
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Impact Toughnness of Chopped Carbon Fiber Reinforced Nylon Fabricated by Material-Extrusion-Based Additive Manufacturing

Abstract: 3D printed polymer composites are gaining more interest due to weight reduction and high geometrical complexity freedom especially for highly demanding applications such as aerospace and defense. Using the material-extrusion based processes, polymer matrix composite parts with complex geometries can be designed and realized to improve the mechanical properties of pure thermoplastic parts. However, in addition to porosity found at the fracture interfaces, the layered nature additive manufacturing processes may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…In contrast, a lower infill density results in lower 3D printing costs and should be seen as an option, if conditions allow it, as seen in a previous study [27]. The filling density has a strong impact on the tensile performance of the sandwich specimens, both on the tensile modulus and on the tensile strength, when its value varies from 20% to 100%, as can be seen in other studies [47][48][49].…”
Section: Tensile Performances Of the Fiber-reinforced Composite Sandw...mentioning
confidence: 53%
“…In contrast, a lower infill density results in lower 3D printing costs and should be seen as an option, if conditions allow it, as seen in a previous study [27]. The filling density has a strong impact on the tensile performance of the sandwich specimens, both on the tensile modulus and on the tensile strength, when its value varies from 20% to 100%, as can be seen in other studies [47][48][49].…”
Section: Tensile Performances Of the Fiber-reinforced Composite Sandw...mentioning
confidence: 53%
“…The other build direction where the tensile direction coincided with the build direction could not be tested due to the specimen’s dimensions exceeding the build direction. Yet, a recent study by Yasa showed that the impact toughness of chopped fiber-reinforced nylon produced in a similar manner to this study was severely affected when the impact was taken in between built layers leading to significant anisotropy in the obtained toughness [12].…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study by Yasa, it was shown that build orientation has a significant influence of carbon-reinforced tough nylon. The impact toughness of specimens built vertically was reduced by 90% in comparison to other directions where the impact was not received in between deposited layers [12].…”
Section: Introductionmentioning
confidence: 99%
“…Yasa and Ersoy [65] investigated that the change of infill percentage from 50% to 75% of the commercial Markforged chopped fibre (Onyx) increases the tensile stiffness about 6%. They continued to study on the infill percentage on toughness and found that the increase in infill from 75% to 100% resulted in a two-fold toughness improvement, but the improvement is insignificant when the shift from 50% to 70% infill [66]. However, the high amount of infill requires a high amount of material and time to complete the part, causing high manufacturing cost [23,67].…”
Section: Infill Volume (%Infill)mentioning
confidence: 99%